2011
DOI: 10.1136/hrt.2009.192104
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan versus imidapril in hypertension: a randomised study to assess effects of anti-AT1 receptor autoantibodies

Abstract: An ARB-based regimen is more effective in BP lowering than an ACE inhibitor-based regimen in the presence of anti-AT1 receptor autoantibodies. Trial registration number This trial has been registered at http://www.register.clinicaltrials.gov/ (identifier: NCT00360763).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 11 publications
(17 reference statements)
0
27
0
Order By: Relevance
“…A recent report of patients with antibody-mediated rejection because of non-DSA antibodies that bind to angiotensin II type I receptors has also been reported and suggests that AT1 receptor blockers might prevent this newly described type of hypertension. [31][32][33] Hypertension associated with acute rejection responds quite well to treatment of rejection, whereas hypertension not associated with acute rejection often is worsened with the addition of or a dose increase in corticosteroids.…”
Section: Donor Factorsmentioning
confidence: 99%
“…A recent report of patients with antibody-mediated rejection because of non-DSA antibodies that bind to angiotensin II type I receptors has also been reported and suggests that AT1 receptor blockers might prevent this newly described type of hypertension. [31][32][33] Hypertension associated with acute rejection responds quite well to treatment of rejection, whereas hypertension not associated with acute rejection often is worsened with the addition of or a dose increase in corticosteroids.…”
Section: Donor Factorsmentioning
confidence: 99%
“…These AT 1 -AAs appear to be similar in function and specificity as those identified in preeclamptic patients as they also bind to the second extracellular loop of the AT 1 R [26, 28]. The fact that essential hypertensive patients with AT 1 -AAs respond with greater blood pressure reductions to AT 1 R blockade by candesartan than hypertensive individuals without AT 1 -AA [29, 30] suggests a causal role for AT 1 -AAs in at least some cases of hypertension.…”
Section: Protein Targets Of Hypertension-related Antibodiesmentioning
confidence: 99%
“…We used losartan, an AT 1 receptor antagonist used to treat hypertention, 18 to demonstrate the presence of AT 1 -AAs in the sera of women with preeclampsia. Our experiments showed that losartan blocked the increase in sEng production and mRNA expression resulting from the treatment with IgG obtained from the sera of the women with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%